Ischemic stroke in a patient with moderate to severe inherited factor VII deficiency. Issue 3 (December 2016) - Reddy, Manasa; Tawfik, Bernard; Gavva, Chakri; Yates, Sean; De Simone, Nicole; Hofmann, Sandra L.; Rambally, Siayareh; Sarode, Ravi
Abstract: Thrombosis is known to occur in patients with rare inherited bleeding disorders, usually in the presence of a thrombotic risk factor such as surgery and/or factor replacement therapy, but sometimes spontaneously. We present the case of a 72-year-old African American male diagnosed with congenital factor VII (FVII) deficiency after presenting with ischemic stroke, presumably embolic, in the setting of atherosclerotic carotid artery stenosis. The patient had an international normalized ratio (INR) of 2.0 at presentation, with FVII activity of 6% and normal Extem clotting time in rotational thromboelastometry. He was treated with aspirin (325 mg daily) and clopidogrel (75 mg daily) with no additional bleeding or thrombotic complications throughout his admission. This case provides further evidence that moderate to severe FVII deficiency does not protect against thrombosis.